Patronage, Weak Institutions, and the Failure to Establish a National Oceangoing Fleet: A Historical Interrogation, 1938-1988 - Poblador, Karl Friedrik K. (Philippine Social Sciences Review; Vol 75 No 1 (2023): PSSR Vol. 75 No. 1 2023, Ed. Jorge V. Tigno, 2025)
When President Corazon Aquino directed the National Development Company (NDC) to transfer its shipping assets to the National Government for eventual privatization in March 1988, the fifty-year effort of the state to participate in the development of a national merchant marine fleet effectively ended. Such an undertaking had been in place since the Commonwealth Period and was meant to make the Philippines competitive as a center for world trade and provide a revenue stream for the government. However, despite the potential of this undertaking and the support of Malacañang, sustained government participation in a national marine fleet never took hold. This paper will, therefore, show how changes in the political landscape got the Government's major stakeholder (the NDC) embroiled in a complex rent-seeking environment that prevented its shipping program from taking off despite the induced demand created by a steady rise in the volume of Philippine exports. It is a testament to how certain historical actors undermined formal institutions and effectively prevented the Philippines from developing an international fleet despite its storied past as a seafaring nation.